From teacher to manager : (Cambridge University Press, 2008)
This is a handbook for managers of language teaching organizations such as Directors and Assistant Directors of Studies, Academic Directors, and School Owners, including those moving into a management role from teaching or administration. It provides an introduction to key concepts required by managers of language teaching organizations, covering topics from strategic and operational financial management, sales and marketing and customer service through to academic and human resource management. This book is also suitable for candidates undertaking the Cambridge ESOL International Diploma in Language Teaching Management (IDLTM).